(untitled) (Bangladesh Journal of Pharmacology, 2008)
Daucus carota Linn. tubers were extracted with water and analyzed for its inotropic and cardioprotective effects by measuring various biochemical parameters at the test doses of 250 and 500 mg/kg. Isoproterenol (5.25 mg/kg and 8.5 mg/kg) was administered subcutaneously on 29th and 30th day respectively in order to induce myocardial infarction. Cardiac tonicity was estimated by evaluating Na+K+ATPase, Mg2+ATPase and Ca2+ATPase levels in heart. The levels of Na+K+ATPase and Mg2+ATPase were decreased and that of Ca2+ATPase was increased in extract-treated group significantly (p<0.001). Cardioprotection was assessed by estimating serum aspartate transaminase, alanine transaminase, lipid peroxidase, and lactate dehydrogenase levels and cardiac total protein and lipid peroxidase, and lactate dehydrogenase. The levels altered by isoproterenol were restored significantly by the administration of the extract. The result of the study implies that D. carota is a potential source to protect heart from myocardial infarction and to maintain its tonicity.